In situ observation of oscillatory redox dynamics of copper - Jing Cao (Nature Portfolio, 2020)
How a catalyst behaves microscopically under reaction conditions, and what kinds of active sites transiently exist on its surface, is still very much a mystery to the scientific community. Here the authors report on in situ observation of a redox active copper catalyst by a combination of in situ imaging and spectroscopy tools.